Synthesis of Antimicrobial Silver Nano Particles from Soil Fungi (International Journal of Scientific Research in Science and Technology, 2024)
The present research was undertaken to synthesize antimicrobial silver Nanoparticles, the growing need of environmental friendly nanoparticles researchers are using several methods for the synthesis of antimicrobial nanoparticles. But nowadays plant extract and soil samples are the agents for the synthesis of nanoparticles. Several Bio-logical systems including Bacteria fungi and yeast have been used in Synthesis of nanoparticles. Silver nano particles have attracted intensive research interest Because of their important application as anti microbial catalytic, textile and plastics to eliminate micro organisms. Fungi are better source for the higher productivity of nanopraticles due to secretion of fairly large amount of proteins. Silver nanoparticles are the leading edge of the rapidly developing field of nano technology. due to its unique properties it is widely used in catalysis chemical sensing and Biosensing, photonics, lectronics, optics and DNA sequencing surface enhanced Raman spectro scopy and pharmaceuticals Nowadays synthesis and characterization of nanoparticles is an important area of research processes synthesis are chemical physical and recently developed biomimetics.